Optimization of Cutting Process Parameters in Inclined Drilling of Inconel 718 Using Finite Element Method and Taguchi Analysis - Pervaiz, Salman (2020)
Nickel-based superalloys are famous in the demanding applications. Inconel 718 is one of the most commonly used nickel-based superalloys due to its extraordinary inherent properties. Inconel 718 is a suitable material for high temperature applications due to the properties such as anti-oxidization, high hot hardness, high creep, and fatigue strength. Drilling operation is one of the most widely used manufacturing operations in almost all industrial sectors. However, drilling operation is very complex in nature due to the presence of intricate geometry of the drill bit. In conventional drilling, cutting is performed by the combined action of the chisel edge and the two or more cutting lips. In depth analysis of the cutting process shows that chisel edge starts with an indentation at the center of the twist drill. Then away from the center, chisel edge performs orthogonal cutting with negative rake angle. Whereas, cutting action at the cutting lip is oblique in nature, and force analysis involves the use of element formulation due to involvement of radius. It is rarely found in the literature where drilling operation at different inclination angles is conducted and analyzed. The presented study numerically investigates the cutting performance of drilling operation, when operated at different inclination angles. The study revealed cutting force variation at different inclination angles due to the different tool workpiece engagement for each inclination. The magnitude of thrust force increased when inclination angle is changed from 30° to 60°. It can be linked with the higher chip load initially in this case as compared to the 30° inclination angle. The cutting temperature was affected by spindle speed (53.7%), followed by feed rate (33.31%) and inclination angle (3.44%).